Introduction to Finance : Markets, Investments, and Financial Management, Fourteenth Edition - Melicher, Ronald; Norton, Edgar (John Wiley and Sons, 2011)
Business managers will gain a basic understanding of the complex world of finance with this engaging book. It presents a balanced survey of the three main areas of finance: institutions and markets, investments, and financial management. The examples have been completely updated throughout to provide the most relevant information. Discussions of small business practice help them gain a better understanding of small business applications. More focus is placed on ethics to reflect the headlines in today's news. Additional end-of-chapter questions and career-profile features also enable business managers to connect the material to the real world.